Phosphorus cycling in the upper waters of the Mediterranean Sea (PEACETIME cruise): relative contribution of external and internal sources - E. Pulido-Villena (Copernicus Publications, 2021)
The study of phosphorus cycling in phosphate-depleted oceanic regions, such as the Mediterranean Sea, has long suffered from methodological limitations, leading to a simplistic view of a homogeneous surface phosphate pool with concentrations below the detection limit of measurement above the phosphacline. During the PEACETIME (Process studies at the air-sea interface after dust deposition in the Mediterranean Sea) cruise, carried out from 10 May to 11 June 2017, we conducted co-located measurements of phosphate pools at the nanomolar level, alkaline phosphatase activities and atmospheric deposition of phosphorus, across a longitudinal gradient from the west to the central Mediterranean Sea. In the phosphate-depleted layer (PDL), between the surface and the phosphacline, nanomolar phosphate was low and showed little variability across the transect spanning from 6 ± 1 nmol L−1 in the Ionian basin to 15 ± 4 nmol L−1 in the westernmost station. The low variability in phosphate concentration contrasted with that of alkaline phosphatase activity, which varied over 1 order of magnitude across the transect. Nanomolar phosphate data revealed gradients of phosphate concentration over density inside the PDL ranging between 10.6 ± 2.2 µmol kg−1 in the westernmost station to values close to zero towards the east. Using the density gradients, we estimated diapycnal fluxes of phosphate to the PDL and compared them to atmospheric deposition, another external source of phosphate to the PDL. Phosphate supply to the PDL from dry deposition and diapycnal fluxes was comparable in the western part of the transect. This result contrasts with the longtime idea that, under stratification conditions, the upper waters of the Mediterranean Sea receive new P almost exclusively from the atmosphere. The contribution of atmospheric deposition to external P supply increased under the occurrence of rain and Saharan dust. Although this finding must be taken cautiously given the uncertainties in the estimation of diapycnal fluxes, it opens exciting questions on the biogeochemical response of the Mediterranean Sea, and more generally of marine oligotrophic regions, to expected changes in atmospheric inputs and stratification regimes. Taken together, external sources of phosphate to the PDL contributed little to total phosphate requirements which were mainly sustained by in situ hydrolysis of dissolved organic phosphorus. The results obtained in this study show a highly dynamic phosphorus pool in the upper layer of the euphotic zone, above the phosphacline, and highlight the convenience of combining highly sensitive measurements and high-resolution sampling to precisely depict the shape of phosphate profiles in the euphotic zone with still unexplored consequences on P fluxes supplying this crucial layer for biogeochemical cycles.